Effects of Parental Depressive Symptoms on Child Adjustment Moderated by Hypothalamic Pituitary Adrenal Activity: Within‐ and Between‐Family Risk. Issue 2 (26th September 2012) - Laurent, Heidemarie K.; Leve, Leslie D.; Neiderhiser, Jenae M.; Natsuaki, Misaki N.; Shaw, Daniel S.; Fisher, Philip A.; Marceau, Kristine; Harold, Gordon T.; Reiss, David
<x xml:space="preserve">Abstract</x> Child hypothalamic pituitary adrenal (HPA) activity was investigated as a moderator of parental depressive symptom effects on child behavior in an adoption sample (n = 210 families). Adoptive parents' depressive symptoms and child internalizing and externalizing were assessed at 18, 27, and 54 months, and child morning and evening HPA activity measured through salivary cortisol at 54 months. Children's daily cortisol levels and day‐to‐day variability were tested as moderators of longitudinal associations between parent and child symptoms at within‐ and between‐family levels. Mothers' symptoms related directly to child internalizing, but child evening cortisol moderated effects of fathers' symptoms on internalizing, and of both parents' symptoms on externalizing. Different paths of within‐family risk dynamics versus between‐family risk synergy were found for internalizing versus externalizing outcomes.